Excess Risk of Dying From Infectious Causes in Those With Type 1 and Type 2 Diabetes. - Magliano, D.; Harding, J.; Cohen, K.; Huxley, Rachel; Davis, W.; Shaw, J. (2015)
OBJECTIVE: To investigate infection-related mortality in individuals with type 1 and type 2 diabetes. RESEARCH DESIGN AND METHODS: A total of 1,108,982 individuals with diabetes who were registered with the Australian Diabetes register between 2000 and 2010 were linked to the National Death Index. Mortality outcomes were defined as infection-related(A-B) death (ICD codes A99-B99), pneumonia (J12-J189), septicemia (A40 and A41), and osteomyelitis (M86). RESULTS: During a median follow-up of 6.7 years, there were 2,891, 2,158, 1,248, and 147 deaths from infection-related(A-B) causes, pneumonia, septicemia, or osteomyelitis, respectively. Crude mortality rates from infections(A-B) were 0.147 and 0.431 per 1,000 person-years in type 1 and type 2 diabetes, respectively. Standardized mortality ratios (SMRs) were higher in type 1 and type 2 diabetes for all outcomes after adjustment for age and sex. For infection-related(A-B) mortality, SMRs were 4.42 (95% CI 3.68-5.34) and 1.47 (1.42-1.53) for type 1 and type 2 diabetes (P < 0.001), respectively. For pneumonia in type 1 diabetes, SMRs were approximately 5 and 6 in males and females, respectively, while the excess risk was ~20% for type 2 (both sexes). For septicemia, SMRs were approximately 10 and 2 for type 1 and type 2 diabetes, respectively, and similar by sex. For osteomyelitis in type 1 diabetes, SMRs were 16 and 58 in males and females, respectively, and ~3 for type 2 diabetes (both sexes). CONCLUSIONS: Although death owing to infection is rare, we confirm that patients with diabetes have an increased mortality from a range of infections, compared with the general population, and that the increased risk appears to be greater for type 1 than type 2 diabetes.